Introducción a las Desigualdades Lineales Matriciales y su Aplicación en Control Automático - Junca Peláez, Mauricio; Grisales Palacio, Victor Hugo; Gauthier Sellier, Alain (Ingeniería, 2004)
This article presents a brief introduction and applications of the linear matrix inequalities in automatic control. This new mathematical technique consists of transforming the control problems to convex optimization problems and to solve them by means of efficient computational algorithms available nowadays. A good number of automatic control problems, for which there are not analytic solution or they don't have it, can be solved by using numeric methods in a reasonable time. In this work they are considered as applications the analysis of quadratic stability as well as the performance specifications in terms of restrictions. These concepts are used to design a control system for an inverted pendulum. The simulation results illustrate the application of the technique and show the fulfillment of the design specifications established.